Market structure, competitive condition, and performance of the global takaful market - Cheong, Sue Sim (2019)
Although the global coverage of the Takaful market has grown substantially since its introduction, there are various aspects of the Takaful market that have not been adequately explored. Studies have previously investigated the organisation structure that influences financial performance, but the market structure and competition on financial performance remain unclear in the Takaful market. Recently, the trend of consolidation and reforms in the global financial service industry has propelled the need to establish a sound and efficient financial system in the insurance industry. Consequently, many of these changes potentially yield significant implications on the involvement and competition, as well as the economic and financial performance of the Takaful market. Therefore, this study is specifically aimed to first, examine the market structure and competitive condition in the Takaful market. In particular, 153 Takaful operators from 14 countries based on availability sampling were included in the analysis. This study assessed the dynamics of the global Takaful market competition from 2008 to 2016 using the Herfindahl-Hirschman Index (HHI) and four-firm concentration ratio (CR4). Furthermore, this study was deemed as the pioneer to examine the competitive condition of the Takaful market using the latest competition indicator, namely the PCS indicator. Overall, the Takaful market was revealed to demonstrate a shift from a highly concentrated market to a moderately concentrated market with a volatile trend of competition. Second, to examine the impact of market structure and competitive condition on the profitability of the Takaful market. The competing and opposing hypotheses that comprised the structure-conduct-performance (SCP) theory, efficient structure (ES) hypothesis, and the theory of relative market power (RMP) were included for analysis, irrespective of whether the profitability of insurers is caused by efficiency due to competition, market structure or individual market power. Using the two-step system Generalized Method of Moments (GMM) estimator, the study obtained empirical evidence that supported the SCP hypothesis. Based on the robust findings, foreign ownership appeared to be the key determinant for the profitability of Takaful operators. With respect to the relationship between the competitive condition and financial stability of the Takaful market, both competition-stability and competition-fragility hypotheses were also tested given their theoretical ambiguity in literature. The obtained results appeared consistent with the competition-stability paradigm and the transmission mechanism hypothesis. Although higher competition in the Takaful market is unable to assist Takaful operators to generate higher profit, it can enhance its market stability. Furthermore, there may be performance differences among Takaful operators according to MENA and non-MENA regions, the types of Takaful business, and ownership structure. Empirical results indicated that a higher market share was found to yield higher profitability for composite and family Takaful operators; thus, supporting the theory of RMP. Meanwhile, the ES hypothesis was only applicable to general Takaful operators. On the other hand, domestic-owned Takaful operators appeared to enjoy higher profitability than foreign-owned Takaful operators; thus, supporting the home field advantage hypothesis. However, there was no evidence that foreign ownership has any significant impact on the stability of Takaful operators. Apart from contributing to the literature, this study obtained essential insights that enhance the understanding of the circumstances of the Takaful market. Given that stability of the Takaful market can be important for policymakers in attempting to accelerate Takaful growth, the results of comparative studies provided significant policy implications for designing and implementing regulations to enhance market efficiency and to safeguard the interests of policyholders, apart from promoting the expansion and stability of the Takaful market.